Investigation of unequal planar wireless electricity device for efficient wireless power transfer - Mohd Hidir, Mohd Salleh; Norhudah, Seman; Dyg Norkhairunnisa, Abang Zaidel; Akaa Agbaeze, Eteng (Czech Technical University, 2017)
This article focuses on the design and investigation of a pair of unequally sized wireless electricity (Witricity) devices that are equipped with integrated planar coil strips. The proposed pair of devices consists of two different square-shaped resonator sizes of 120 mm × 120 mm and 80 mm × 80 mm, acting as a transmitter and receiver, respectively. The devices are designed, simulated and optimized using the CST Microwave Studio software prior to being fabricated and verified using a vector network analyzer (VNA). The surface current results of the coupled devices indicate a good current density at 10 mm to 30 mm distance range. This good current density demonstrates that the coupled devices' surface has more electric current per unit area, which leads to a good performance up to 30 mm range. Hence, the results also reveal good coupling efficiency between the coupled devices, which is approximately 54.5 % at up to a 30 mm distance, with both devices axially aligned. In addition, a coupling efficiency of 50 % is achieved when a maximum lateral misalignment (LM) of 10 mm, and a varied angular misalignment (AM) from 0° to 40° are implemented to the proposed device.